STUDI EVALUASI SISTEM PENGUMPULAN, PEWADAHAN, PENYIMPANAN DAN PENGANGKUTAN LIMBAH PADAT B3 (STUDI KASUS PT. PHAPROS TBK SEMARANG) - Priyambada, Ika Bagus; Amelia, Eliza Bhakti (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2006)
Every industry has a potential to pruduce waste from its production processes. Waste defined as  unused material  coming  from  the  production  activity.  Type  of  industrial  waste  may  vary depend on production activity, such as raw material, type  of processes, including type of raw material used, machinary, which will influence the characteristic of waste itself. Pharmaceutical industry, within their production activity will produce waste which may be potential for harming the environment. The waste may in form of toxic or non toxic chemical substances in both solid or liquid waste. Most of the waste characterize as hazardous waste and need further treatment due to avoid environmental hazard. Hazardous waste from pharmaceutical industry are in form of sludge from waste water treatment plant (WWTP), rejected material and also used container.